In vitro Methods to Cultivate Spiral Ganglion Cells, and Purification of Cellular Subtypes for Induced Neuronal Reprogramming - Meas, Steven J.; Nishimura, Koji; Scheibinger, Mirko; Dabdoub, Alain (Frontiers in Neuroscience, 2018)
Hearing loss can develop as a consequence of primary auditory neuron degeneration. These neurons are present within the spiral ganglion of the inner ear and co-exist with glial cells that assist in neuronal maintenance and function. There are limited interventions for individuals with hearing impairment, hence novel biological solutions must be explored. Regenerative strategies can benefit from in vitro methods to examine the long-term culture of purified cell populations. The culturing of neuronal, glial, and non-neuronal, non-glial cell types in both neonatal and adult mice is presented along with the whole-organ explant culture of the spiral ganglion. High yields of spiral ganglion glial and non-glial cells were cultured from both neonatal and adult mice. Dissociated spiral ganglion cells from Sox2-EGFP mice were sorted based on EGFP expression using fluorescence activated cell sorting. The EGFP+ fraction included purified glial populations, whereas the EGFP- fraction contained non-glial cells. Purified glial cells could be reprogrammed into induced neurons displaying neuronal markers and morphology at a higher efficiency than non-glial cells. Previous studies have only allowed for the short-term culturing of spiral ganglion cell populations and have placed emphasis on neonatal cells. There has also been a lack of methods able to cultivate pure cell populations. Here, the coupling of transgenic mouse lines, fluorescence activated cell sorting and advanced culture conditions allow cultivation and characterization of neuronal, glial and non-neuronal, non-glial cells from the spiral ganglion. These techniques are used to demonstrate that different spiral ganglion cell subtypes (glial vs non-glial) display different competencies for direct neuronal reprogramming.